Transcriptional analysis of microRNAs related to unsaturated fatty acid synthesis by interfering bovine adipocyte ACSL1 gene - Li, Xupeng; Bai, Yanbin; Li, Jingsheng; Chen, Zongchang; Ma, Yong; Shi, Bingang; Han, Xiangmin; Luo, Yuzhu; Hu, Jiang; Wang, Jiqing; Liu, Xiu; Li, Shaobin; et al. (Frontiers in Genetics, 2022)
Long-chain fatty acyl-CoA synthase 1 (ACSL1) plays a key role in the synthesis and metabolism of fatty acids. The proportion of high unsaturated fatty acids in beef not only affects the flavor but improves the nutritional value of the meat. In this study, we used RNA-Seq technology to identify miRNAs related to unsaturated fatty acid synthesis by interfering with ACSL1 and not interfering with ACSL1 gene. A total of 1075 miRNAs were characterized as differentially expressed miRNAs (DE-miRNAs), of which, 16 were up-regulated and 12 were down-regulated miRNAs. GO (Gene ontology) analysis indicated that the target genes of DE-miRNAs were mainly involved in biological regulation and metabolic processes. Additionally, KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis identified that the target genes of DE-miRNAs were mainly enriched in metabolic pathways, fatty acid metabolism, PI3K-Akt signaling pathway, glycerophospholipid metabolism, fatty acid elongation and glucagon signaling pathway. Moreover, through the miRNA-mRNA interaction network, we screened out several key miRNA-mRNA targeting relationship pairs, novel-m0035-5p—ACSL1, novel-m0035-5p—ELOVL4, miR-9-X—ACSL1, bta-miR-677—ACSL1, miR-129-X—ELOVL4 and bta-miR-485—FADS2. The results of this study provide a theoretical basis for further research on miRNA regulation of unsaturated fatty acid (UFA) synthesis in bovine adipocytes.